(untitled) (International journal of artificial intelligence, 2025)
This article looks at the ecofeminist ideas in the novels of Barbara Kingsolver. Her writing shows how the problems of women and the environment are connected. By reading her books like The Bean Trees, Animal Dreams, Prodigal Summer, and Flight Behavior, we can see how she presents relationships between people, nature, and society. The study uses different kinds of ecofeminist theory, such as cultural, materialist, and intersectional ecofeminism, to understand her message. Kingsolver’s stories show strong women who protect nature and fight against unfair systems. Through her characters, symbols, and natural settings, her novels give a strong voice to ecofeminist thinking.